2015
DOI: 10.5006/1806
|View full text |Cite
|
Sign up to set email alerts
|

Stress corrosion cracking of ferritic-maretensitic steels in simulated boiling water reactor environment

Abstract: Stress corrosion cracking of APMT (Advanced Powder Metallurgy Technology) and T91 (ferritic-martensitic) steels were investigated in the as-received and proton-irradiated conditions in simulated boiling water reactor environment (2 ppm O 2 ) using constant extension tensile tests at 288°C at a strain rate of 3×10 -7 s -1 . Significant stress corrosion cracking was not observed in the as-received condition. A few cracks, perpendicular the loading direction, were observed in the proton-irradiated (5 dpa) specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…The alloy exhibited the highest degree of uniform plastic deformation of any alloy tested when it was tested at high temperature. Furthermore, it showed signs of dynamic strain aging, a result consistent with previous findings for different heats of Kanthal APMT [14,23,24]. Fracture surfaces in the specimens tested at room temperature showed trademark transgranular fracture with faceted textures and river markings ( Figure 2c).…”
Section: Unirradiated Tensile Propertiessupporting
confidence: 89%
See 2 more Smart Citations
“…The alloy exhibited the highest degree of uniform plastic deformation of any alloy tested when it was tested at high temperature. Furthermore, it showed signs of dynamic strain aging, a result consistent with previous findings for different heats of Kanthal APMT [14,23,24]. Fracture surfaces in the specimens tested at room temperature showed trademark transgranular fracture with faceted textures and river markings ( Figure 2c).…”
Section: Unirradiated Tensile Propertiessupporting
confidence: 89%
“…Retained ductility has direct implications in the performance of cladding under operation especially when subjected to pellet-cladding mechanical interaction. The similar mechanical performance, especially in relation to ductility, between both alloy classes, the retained deformability in the lower Cr FeCrAl alloys indicated by the reduction-of-area results in Figure 8, and limited susceptibly of FeCrAl alloys to corrosion-assisted embrittlement [14,38,39] suggests the applicability of FeCrAl alloys as ATF LWR cladding from the standpoint of tensile properties under irradiation. Other mechanical properties, such as thermal creep and irradiation creep, should be determined prior to conclusively determining commercial use of any FeCrAl alloy as ATF LWR cladding.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Because of its ferritic or bcc structure, FeCrAl alloys are also more resistant to irradiation degradation than prior versions of austenitic SS cladding materials. Proton irradiation studies performed at the U. of Michigan showed that FeCrAl materials may be resistant to proton irradiation induced cracking providing additional confirmation of the potential acceptability of FeCrAl materials for fuel rod cladding [12]. Although there may be nominal changes in fuel rod geometry (e.g.…”
Section: Accident Tolerant Fuels (Atf)mentioning
confidence: 90%
“…For high-Cr ferritic steels, including FeCrAl alloys, limited studies have been completed. Currently, the only known work on SCC of FeCrAl alloys has been completed on Kanthal APMT by Andresen et al/Rebak [84,85] and by Ahmedabadi and Was [86]. The study of Ahmedabadi and…”
Section: Stress Corrosion Crackingmentioning
confidence: 99%